Bottom‐up and top‐down proteomic approaches for the identification, characterization, and quantification of the low molecular weight proteome with focus on short open reading frame‐encoded peptides. Issue 23 (26th June 2021) - Cassidy, Liam; Kaulich, Philipp T.; Maaß, Sandra; Bartel, Jürgen; Becher, Dörte; Tholey, Andreas
Abstract: The recent discovery of alternative open reading frames creates a need for suitable analytical approaches to verify their translation and to characterize the corresponding gene products at the molecular level. As the analysis of small proteins within a background proteome by means of classical bottom‐up proteomics is challenging, method development for the analysis of small open reading frame encoded peptides (SEPs) have become a focal point for research. Here, we highlight bottom‐up and top‐down proteomics approaches established for the analysis of SEPs in both pro‐ and eukaryotes. Major steps of analysis, including sample preparation and (small) proteome isolation, separation and mass spectrometry, data interpretation and quality control, quantification, the analysis of post‐translational modifications, and exploration of functional aspects of the SEPs by means of proteomics technologies are described. These methods do not exclusively cover the analytics of SEPs but simultaneously include the low molecular weight proteome, and moreover, can also be used for the proteome‐wide analysis of proteolytic processing events.